Clinical usefulness of fixation of absorbable implants with cyanoacrylate in comminuted fractures of the maxilla - Ju, Gang San; Son, Kyung Min; Choi, Woo Young; Cheon, Ji Seon (Archives of craniofacial surgery, 2019)
The open reduction of craniofacial bone fractures requires internal fixation using metal plates and screws, which have been considered the gold standard. However, metal implants pose a risk of palpation, protrusion, and foreign body reaction, and they may require an additional operation for removal. Recently, good results have been reported for absorbable implants which complement the disadvantages of metal implants. This study presents the results of using absorbable mesh, plates, and screws with cyanoacrylate for more accurate and firmer fixation of comminuted fractures of the maxilla. In total, 235 patients underwent operations for comminuted fractures of the maxilla. From January 2012 to December 2014, absorbable mesh and screws were used in 114 patients, while from January 2015 to December 2017, absorbable mesh, plates, and screws with cyanoacrylate were used in 121 patients. Open reduction of the bone fragments was performed, after which absorbable implants were accurately molded and fixed by screws. All patients underwent postoperative computed tomography scans, which showed highly accurate reduction and firm fixation in the patients who underwent procedures using absorbable implants, screws, and cyanoacrylate. There were no postoperative complications or cases of abnormal facial contour. When absorbable implants and screws are used for maxillary fractures, no additional surgery to remove the metal plate is required. In addition, the use of cyanoacrylate enables accurate and firm fixation of the tiny bone fragments that cannot be fixed with screws.